Synthesis of novel β-lactam-fused 1, 5-benzothiazepine derivatives bearing quinoline moiety. (2nd January 2016) - Zeng, Yongming; Zeng, Hehua; Zhang, Hongxi; Geng, Lili; Zhao, Xiufeng; Cheng, Jianwen
GRAPHICAL ABSTRACT: Abstract: A series of β-lactam-fused 1, 5-benzothiazepine derivatives containing the quinoline moiety were synthesized via [2 + 2] cycloadditions reaction and the structures of the target compounds were confirmed by spectroscopic methods. These tricyclic heterocycles are promising candidates for drug discovery.